Pediatric tuberculosis on isolated island: a case study from Masalembu Island, Indonesia - Muhammad Abbud Widitaputra; Retno Asih Setyoningrum; Agus Harianto (Zdorovʹe Rebenka)
Tuberculosis, caused by Mycobacterium tuberculosis, is transmitted through the release of bacteria into the air via respiratory activities, such as breathing and coughing. Untreated latent tuberculosis can act as a reservoir for future infections. Remote regions like Masalembu encounter additional challenges, including shortages of healthcare professionals, inadequate infrastructure, and restricted access to healthcare services. An 8-year-old boy, identified during active case finding conducted by the Ksatria Airlangga Hospital Ship, had been in contact with his father, who had bacteriologically confirmed tuberculosis and was undergoing five months of therapy. The child presented with prolonged cough and malnutrition. Notably, no Bacillus Calmette-Guérin vaccination scar was observed, the tuberculin skin test was positive, and rapid molecular testing yielded negative results. Diagnosis was established using the Indonesian tuberculosis scoring system, and the patient commenced a six-month treatment. Several factors contribute to diagnostic delays, including nonspecific symptoms, inadequate infrastructure, and limited capacity to perform diagnostic procedures, such as gastric aspiration and sputum induction, suboptimal contact tracing, incomplete immunization, and geographic isolation. The involvement of government entities, healthcare professionals, and the community is crucial in addressing pediatric tuberculosis. Emphasizing strategies like enhancing contact tracing could significantly improve tuberculosis management in isolated island communities.